Impact of tubulointerstitial lesions on anaemia in patients with biopsy‐proven diabetic nephropathy. Issue 4 (16th December 2014) - Mise, K.; Hoshino, J.; Ueno, T.; Imafuku, A.; Kawada, M.; Sumida, K.; Hiramatsu, R.; Hasegawa, E.; Yamanouchi, M.; Hayami, N.; Suwabe, T.; Sawa, N.; et al.
Abstract: Aims: To investigate the relationship between the progression of anaemia and renal pathological findings in patients with diabetic nephropathy. Methods: A total of 223 patients with diabetes underwent renal biopsy from 1985 to 2010 and were confirmed to have pure diabetic nephropathy according to the recent classification, of whom 113 (baseline haemoglobin ≥ 11 g/dl) were enrolled in the study. Linear regression analysis was used to estimate the changes in haemoglobin levels during the follow‐up period. Results: In a multivariate model adjusted for clinical and histopathological variables, higher interstitial fibrosis and tubular atrophy scores were more strongly associated with a decrease in haemoglobin levels than were lower scores. Compared with an interstitial fibrosis and tubular atrophy score of 0, the standardized coefficients for interstitial fibrosis and tubular atrophy scores of 1, 2 and 3 were 0.20 (95% CI −0.31 to 0.93), 0.34 (95% CI −0.22 to 1.34) and 0.47 (95% CI 0.07 to 1.96), respectively, whereas a higher glomerular class, a higher vascular lesion score and the presence of exudative lesions were not strongly correlated with the decrease in haemoglobin. Conclusions: Tubulointerstitial lesions that are more advanced are significantly associated with the progression of anaemia in patients with diabetic nephropathy after adjustment for numerous covariates. This finding suggests that tubulointerstitial lesions may be a useful prognostic indicator for anaemia in patients with diabetic nephropathy, and that decreased erythropoietin production attributable to the progression of tubulointerstitial lesions is a major cause of anaemia in these patients. What's new?: The relationship between progression of anaemia and renal pathological findings was investigated in patients with biopsy‐proven diabetic nephropathy. Tubulointerstitial lesions that were more advanced were significantly associated with the decrease of haemoglobin after adjustment for numerous covariates. This finding suggests that tubulointerstitial lesions may be a useful prognostic indicator for anaemia in patients with diabetic nephropathy, and that decreased erythropoietin production as a result of progression of tubulointerstitial lesions is a major cause of anaemia in these patients.